Endemic birds of the Atlantic Forest: traits, conservation status, and patterns of biodiversity. Issue 3 (23rd September 2018) - Vale, Mariana M.; Tourinho, Luara; Lorini, Maria Lucia; Rajão, Henrique; Figueiredo, Marcos S. L.
Abstract: The bird fauna of the Brazilian Atlantic Forest is exceptionally diverse and threatened, with high levels of endemism. Available lists of the endemic birds of the Atlantic Forest were generated before recent taxonomic revisions lumped or split species and before the recent increase in species occurrence records. Our objective, therefore, was to compile a new list of the endemic birds of the Atlantic Forest, characterize these species in terms of conservation status and natural history traits, and map remaining vegetation and protected areas. We combined GIS analysis with a literature search to compile a list of endemic species and, based on the phylogeny and distribution of these species, characterized areas in terms of species richness, phylogenetic diversity, and endemism. We identified 223 species of birds endemic to the Atlantic Forest, including 12 species not included in previous lists. In addition, 14 species included in previous lists were not considered endemic, either because they occur outside the Atlantic Forest biome or because they are not considered valid species. The typical Atlantic Forest endemic bird is a small forest‐dependent invertivore. Of the species on our list, 31% are considered threatened or extinct. Only 34% of the spatial analysis units had > 10% forest cover, and protected area coverage was consistently low (< 1%). In addition, we found spatial incongruity among the different measures of biodiversity (species richness, relative phylogenetic diversity, restricted‐range species, and irreplaceability). Each of these measures provides information concerning different aspects of biological diversity. However, regardless of which aspect(s) of biodiversity might be considered most important, preservation of the remaining areas of remnant vegetation and further expansion of protected areas are essential if we are to conserve the many endemic species of birds in the Atlantic Forest.